Effects of circuit albumin coating on coagulation and inflammatory response for patients receiving aortic arch replacement: a randomized controlled trial. (October 2016) - Chen, Liang; Lv, Lin; Long, Cun; Lou, Song
Objective: To investigate whether human serum albumin coating before cardiopulmonary bypass (CPB) could improve platelet function and hemostasis and mitigate the inflammatory response among patients receiving aortic arch replacement with deep hypothermic circulatory arrest (DHCA). Methods: Sixty patients were included and randomized into two groups: the Control Group (CG, receiving 40 g human albumin 5 minutes after the initiation of CPB) and the Study Group (SG, circulating the prime with 40 g albumin for 5 minutes before CPB). Rapid thromboelastography, complete blood count, coagulation tests and cytokines (IL-1, IL-6, IL-10, TNF-α and PAF) were measured at two intervals: after anesthesia induction and before CPB (T1) and 10 minutes after heparin reversal before any blood product transfusion (T2). Results: Compared with T1, the fibrinogen and MA levels in both groups reduced significantly after heparin reversal and fell within the normal range for most patients. The platelet count reduction (ΔPLT) in the Study Group was significantly less than in the Control Group (p=0.031). Despite the inflammatory factor levels increasing after CPB (p<0.001), no differences were found between the Control Group and the Study Group. Fewer red blood cells were given in the Study Group, but this was not significant (p=0.05). Conclusion: Most patients receiving aortic arch replacement with DHCA have normal platelet function and fibrinogen levels after heparin reversal. Albumin coating before CPB may mitigate the platelet count reduction, but not platelet dysfunction. There is a trend that the patients treated with albumin coating received less red blood cell transfusions.